2004
DOI: 10.1097/00004691-200405000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Studies of Skilled Psychomotor Performance

Abstract: Measurements based on the EEG have featured prominently in shaping present-day concepts of the neurocognitive aspects of skilled performance. The techniques include measurements of spectral power, interelectrode coherence, event-related potential components such as the P300, slow potentials, and the method of cognitive inference. The advantages offered by EEG-based approaches lies in their spatiotemporal resolution (potentially 1 mm and less than 1 millisecond, respectively) and the potential to preserve ecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
113
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 35 publications
17
113
2
7
Order By: Relevance
“…Our kinematics and EEG results suggest that better performers were associated with, not only enhancement of activation (stronger alpha ERD) during training, but also with decreased neural activations (greater beta ERS) during movement execution, which might be reflective of greater neural efficiency in the brain networks underlying performance [107,108]. This suggests a more efficient neural code for controlling the motor movement and is consistent with the enhancement of beta synchronization following successful movement [109,110], particularly during gross movements such as the wrist [111], as well as improved motor performance [82].…”
Section: Discussionmentioning
confidence: 73%
“…Our kinematics and EEG results suggest that better performers were associated with, not only enhancement of activation (stronger alpha ERD) during training, but also with decreased neural activations (greater beta ERS) during movement execution, which might be reflective of greater neural efficiency in the brain networks underlying performance [107,108]. This suggests a more efficient neural code for controlling the motor movement and is consistent with the enhancement of beta synchronization following successful movement [109,110], particularly during gross movements such as the wrist [111], as well as improved motor performance [82].…”
Section: Discussionmentioning
confidence: 73%
“…As previously mentioned, although several methods can be used to isolate some specific frequency bands; one of the main problems of the EEG/MEG spectral analysis is the definition of the upper and lower bounds of the bands (Pfurtscheller & Lopes da Silva, 1999). Although the definition of the frequency band limits can slightly differ from one study to another, a possible approach for partitioning the frequency bands related to human motor performance for healthy adults is to consider the theta ([4-7 Hz]), alpha (8)(9)(10)(11)(12)(13)), beta ) and gamma (36)(37)(38)(39)(40)(41)(42)(43)(44)) frequency bands (e.g., Hatfield et al, 2004;Haufler et al, 2000;Tombini et al, 2009). Sometimes, the frequency range spread from 8 to 15 Hz (Blankertz & Vidaurre, 2009) or from 9 to 13Hz Pfurtscheller & Neuper, 1997) are also named alpha frequency (or mu rhythm under certain conditions).…”
Section: Erd/ers Methodsmentioning
confidence: 99%
“…Sometimes, the frequency range spread from 8 to 15 Hz (Blankertz & Vidaurre, 2009) or from 9 to 13Hz Pfurtscheller & Neuper, 1997) are also named alpha frequency (or mu rhythm under certain conditions). Moreover, since it has been shown that certain frequency sub-bands are related to specific brain states during a sensorimotor task (e.g., Contreras-Vidal et al, 2004;Gentili et al, 2008;Hatfield et al, 2004;Tombini et al, 2009), most of the EEG/MEG studies refined their analysis by considering sub-frequency bands, typically, the low and high component of the original entire band. Therefore, for the bands previously defined, the low theta ([4-5 Hz]), high theta ([6-7 Hz]), low alpha ([8-10 Hz]), high alpha (11)(12)(13)), low beta (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)) and high beta (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)) frequency bands can also be considered.…”
Section: Erd/ers Methodsmentioning
confidence: 99%
See 2 more Smart Citations